Are All Inside Directors the Same? Evidence from the External Directorship Market - MASULIS, RONALD W.; MOBBS, SHAWN (Journal of Finance, 2011)
ABSTRACT Agency theory and optimal contracting theory posit opposing roles and shareholder wealth effects for corporate inside directors. We evaluate these theories using the market for outside directorships to differentiate among inside directors. Firms with inside directors holding outside directorships have better operating performance and market‐to‐book ratios, especially when monitoring is more difficult. These firms make better acquisition decisions, have greater cash holdings, and overstate earnings less often. Announcements of outside board appointments improve shareholder wealth, while departure announcements reduce it, consistent with these inside directors improving board performance and outside directorships being an important source of inside director incentives.